(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the application of mathematical methods for the optimal management of irrigation systems and the rational distribution of water resources in technical and engineering education. The study emphasizes that irrigation management requires not only hydraulic and agronomic knowledge, but also mathematical modeling, optimization algorithms, statistical analysis, forecasting techniques, and decision-support approaches. In conditions of increasing water demand, climate variability, uneven seasonal water availability, and the need to improve agricultural productivity, mathematical methods become an important tool for planning water allocation, reducing losses, and improving the efficiency of irrigation infrastructure. The article analyzes the role of linear programming, dynamic programming, simulation modeling, multi-criteria decision-making, water balance equations, and predictive models in organizing effective irrigation schedules and resource distribution. Special attention is given to the integration of mathematical models with digital monitoring systems, remote sensing data, and automated control technologies. The research shows that mathematical approaches help determine optimal irrigation norms, prioritize water supply among users, minimize operational costs, and support environmentally responsible water management. The article concludes that the systematic use of mathematical methods in irrigation engineering contributes to sustainable resource use, technological modernization, and the development of scientifically grounded water management strategies.